Growth of well-ordered iron sulfide thin films. Issue 36 (5th September 2019) - Davis, Earl Matthew; Berti, Giulia; Kuhlenbeck, Helmut; Vonk, Vedran; Stierle, Andreas; Freund, Hans-Joachim
Abstract : Preparation and structural analysis of well-ordered, single-crystalline, hexagonal iron sulfide thin films for use in model catalysis studies. Abstract : In this paper a growth recipe for well-ordered iron sulfide films and the results of their characterisation are presented. The film was studied using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low energy electron diffraction (LEED), and scanning tunneling microscopy (STM). XRD data reveal that the film has a NiAs-like structure with Fe vacancies, similar to iron sulfides such as pyrrhotite and smythite, although no indication of any ordering of these vacancies was observed. LEED and STM results show that the film exhibits a 2 × 2 surface reconstruction. XPS data provide additional evidence for a large number of Fe vacancies, and the oxidation states of the Fe and S in the film are analysed.